1996
DOI: 10.1046/j.1365-313x.1996.10030437.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated silencing and reactivation of tobacco chitinase transgene expression

Abstract: The tobacco class I chitinase gene CHN48 driven by CaMV 35S RNA expression signals introduced into Nicotiana sylvestris can inactivate its own expression as well as expression of homologous host genes at the mRNA level. Comparison of the silencing of chitinase and β‐1,3‐glucanase transgenes with the same expression signals and breeding experiments with transgenes inserted in different chromosomes showed that chitinase‐gene silencing depends on transcribed sequence hornology and trans‐gene dose. The CHN48 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
99
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 0 publications
11
99
1
Order By: Relevance
“…4), where the silencing is triggered simultaneously both in inoculated and non-inoculated plants, and seems to occur at a certain developmental stage. A similar example of development-associated silencing has been reported recently for a viral transgene, the tospoviral N gene (Pang et al, 1996) and there are also examples of this phenomenon for non-viral transgenes (Elmayan & Vaucheret, 1996 ;Kunz et al, 1996). TVMV infection of our P3 lines may have an overlapping role resulting in a final degree of gene silencing that is more complete in inoculated than uninoculated plants (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…4), where the silencing is triggered simultaneously both in inoculated and non-inoculated plants, and seems to occur at a certain developmental stage. A similar example of development-associated silencing has been reported recently for a viral transgene, the tospoviral N gene (Pang et al, 1996) and there are also examples of this phenomenon for non-viral transgenes (Elmayan & Vaucheret, 1996 ;Kunz et al, 1996). TVMV infection of our P3 lines may have an overlapping role resulting in a final degree of gene silencing that is more complete in inoculated than uninoculated plants (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Earlier we showed that all members of the CHN and GLU gene families can be posttranscriptionally silenced in sense Nicotiana sylvestris transformants (25)(26)(27). Here we report that posttranscriptional sense-and antisense-silencing of these genes in tobacco is suppressed by plant viruses known to suppress PTGS and that smRNAs diagnostic for PTGS (7) are associated with both forms of silencing.…”
mentioning
confidence: 66%
“…Plants at the six-leaf stage were assayed for expression of the silent and high-expressing phenotypes as described (25). A fully expanded leaf of plants with ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another, indirect indication for the importance of chitinases during seed development comes from a recent study of tobacco plants with low chitinase levels because of silencing caused by transgene expression of a tobacco class I chitinase. The silenced chitinases were transiently reset to a high-expressing state 8 to 11 DAP (Kunz et al, 1996). An explanation for the resetting of the silenced chitinases was not given, but it cannot be excluded that the requirement for chitinases during this period in seed development is a driving force for the resetting.…”
Section: Discussionmentioning
confidence: 98%